STUDENTS’ VOICES ON TRANSLINGUAL PRACTICES WITHIN EFL CLASSROOM - Umam, Akhmad Hairul (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2023)
This study investigated students’ voices on translingual practices within an EFL classroom by involving 47 students in higher education. This study used a descriptive qualitative approach in which the data were collected through recording of teaching language learning activities, surveys, and interviews. Students were asked several questions about their voices and learning experiences regarding translingual practices in an EFL classroom. The findings showed that students’ voices on translingual practices within an EFL classroom varied, depending on personal circumstances, linguistic background, and learning experiences. Most of the students had a favorable opinion of the translingual practices and said that it was an accommodating strategy that allowed them to actively and confidently take part in the language learning activities. Students benefited from and valued the chances offered by translingual activities within an EFL which were very helpful in acquiring the target language. Moreover, this bridged students and teachers to create dynamic and fluid interactions in English learning.